Novel Results on D-Soft Compact Spaces (European Journal of Pure and Applied Mathematics, 2025)
This paper introduces and investigates D-soft compact spaces, a novel generalization of compactness in soft topological spaces using D-soft covers. We establish fundamental properties, characterizations, and relationships between D-soft compactness and other forms of soft compactness. Key results include the hereditary nature of D-soft compactness under specific conditions, the equivalence between D-soft and soft compactness in soft locally indiscrete spaces, and preservation under continuous mappings. The study provides new perspectives on compactness conditions in soft topology with potential applications in decision-making and uncertainty modeling. Several examples and counterexamples illustrate the theoretical developments, demonstrating that D-soft compactness is generally stronger than soft compactness.